Mental health care in Italy: Basaglia's ashes in the wind of the crisis of the last decade. (June 2020) - Carta, Mauro G; Angermeyer, Matthias C; Holzinger, Anita
Background and Aims: The purpose is to highlight the legal and ethical principles that inspired the reform of mental health care in Italy, the only country to have closed its psychiatric hospitals. The article will also try to verify some macro-indicators of the quality of care and discuss the crisis that the mental health care system in Italy is experiencing. Methods: Narrative review. Results: The principal changes in the legislation on mental health care in Italy assumed an important role in the evolution of morals and common sense of the civil society of that country. We describe three critical points: first, the differences in implementation in the different Italian regions; second, the progressive lack of resources that cannot be totally attributed to the economic crisis and which has compromised application of the law; and finally, the scarce attention given to measurement of change with scientific methods. Conclusion: Italy created a revolutionary approach to mental health care in a historical framework in which it produced impressive cultural expressions in many fields. At that time, people were accustomed to 'believing and doing' rather than questioning results and producing research, and this led to underestimating the importance of a scientific approach. With its economic and cultural crisis, Italy has lost creativity as well as interest in mental health, which has been guiltily neglected. Any future humanitarian approach to mental health must take the Italian experience into account, but must not forget that verification is the basis for any transformation in health care culture.